2019
DOI: 10.1111/bjet.12888
|View full text |Cite
|
Sign up to set email alerts
|

Building the role of ICT coordinators in primary schools: A typology based on task prioritisation

Abstract: Although the school ICT coordinator's role has been institutionally defined by the Andalusian Education Administration (Spain), individual factors may be key in the emerging role-building process. Multidimensional scaling (MDS) of the priority given by coordinators to their different functions and a subsequent cluster analysis of the MDS solution were used to identify role orientations among ICT coordinators in primary schools of Andalucía (Spain). Three orientation clusters were identified: "support of ICT us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…The improvement of teaching and learning practices through the implementation of information and communications technologies (ICTs) is a goal of increasing importance, evidenced by national programs to provide schools with ICT infrastructure (Skues and Cunningham, 2013), and to adapt education systems to the 21st century (Avidov-Ungar and Shamir-Inbal, 2017). It is also clear that ICT implementation is a complex process (León-Jariego et al, 2020) as studies have shown many regions neither systematically nor in a systemic way have achieved ICT implementation (McDonagh and McGarr, 2015; Skues and Cunningham, 2013; Tondeur et al, 2010). Many people must participate to realize full ICT implementation in schools (Murphy et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The improvement of teaching and learning practices through the implementation of information and communications technologies (ICTs) is a goal of increasing importance, evidenced by national programs to provide schools with ICT infrastructure (Skues and Cunningham, 2013), and to adapt education systems to the 21st century (Avidov-Ungar and Shamir-Inbal, 2017). It is also clear that ICT implementation is a complex process (León-Jariego et al, 2020) as studies have shown many regions neither systematically nor in a systemic way have achieved ICT implementation (McDonagh and McGarr, 2015; Skues and Cunningham, 2013; Tondeur et al, 2010). Many people must participate to realize full ICT implementation in schools (Murphy et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Within the past decade, regions in Australia (Skues and Cunningham, 2013), Ireland (McDonagh and McGarr, 2015) and the United States (Murphy et al, 2017) have not had an ICT coordinator role in schools. While there are claims the role is widespread in Spain (Moreira et al, 2018), there is also evidence that some Spanish schools lack the role, and the availability of the role varies by region (León-Jariego et al, 2020). The role can also be non-permanent, as Tondeur et al (2010) found that some schools have lost the ICT coordinator role without sufficient, external support.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations